The moderators affect on social media addiction globally - Leong, See Kei (2023)
Social media addiction defined as being too worried about social networking sites and visiting it frequently on a daily basis in which this behavior started to interfere with one’s social activity, interpersonal relationship and mental health as well as general wellbeing. Against these backgrounds, this study aims to determine the factors which would affect one’s addiction level in social media. Besides, this study aims to identify does the demographic factors of an individual affect their level of addiction towards social media. By using the secondary data obtained from Pew Research Centre (2021) for analysis, the findings indicate that the social networking sites, type of connection and the cost of connection could affect the level of addiction of an individual. Also, the result asserted that female, individual with lower education level and individual with lower income level are prone to have social media addiction. The findings of this study have contributed some valuable insights and implications to the literature regarding the understanding of social media addiction.